An integrated organic farming system: innovations for farm diversification, sustainability, and livelihood improvement of hill farmers - Layek, Jayanta; Das, Anup; Ansari, Meraj A.; Mishra, Vinay K.; Rangappa, Krishnappa; Ravisankar, Natesan; Patra, Sandip; Baiswar, Pankaj; Ramesh, Thangam; Hazarika, Samarendra; Panwar, Azad S.; Devi, Shidayaichenbi; et al. (Frontiers in Sustainable Food Systems, 2023)
Organic farming is a promising solution for mitigating environmental burdens related to input-intensive agricultural practices. The major challenge in organic agriculture is the non-availability of large quantities of organic inputs required for crop nutrition and sustaining soil health, which can be resolved by efficient recycling of the available on and off-farm resources and integrated approach. Integrated organic farming system (IOFS) model comprising agricultural and horticultural crops, rainwater harvesting unit, livestock components, and provisions for nutrient recycling unit have been developed and disseminated in adopted organic villages. Harvested rainwater in farm ponds and jalkund was used for live-saving irrigation in winter months and diversified homestead farming. The yield of crops and vegetables grown under the IOFS models enhanced by 20-30, 40-45, 33-40, 45-50, 37-50, and 27-30%, respectively over their traditional practices. The income from the livestock component ranged from 41 to 49 % and for fishery ranged from 3.5 to 9.5%, fruits component ranging from 5 to 7%. Some farmers produced vermicompost in verimibeds and cement brick chambers and produced 0.4 to 1.25 tonnes per annum. Two individual farmers, Mr. Jrill Makroh and Mrs. Skola Kurbah obtained net returns (without premium price) of Rs. 46,695±418 and Rs. 31,102±501 from their respective 0.27 and 0.21 ha IOFS models which is equivalent to Rs. 1,72,944±1548/ha/year and Rs. 1,48,105±2385/ha/year, respectively. The net return obtained from the IOFS models were significantly higher as compared to the farmers’ practice of maize-fallow or cultivation of maize followed by vegetable 30% of the areas. It is expected that, with the certification of organic products, the income as well as the livelihood of the farmers, will be further improved over the years. While the model of Mr. Jril Makhroh could supply 95.1% of N, 82.0% of P2O5, and 96.0 % of the total K2O requirement of the system, Mrs. Skola Kurbah’s model can generate 76.0% of total N, 68.6% of P2O5 and 85.5% of total K2O requirement for the system. Thus, promotion of IOFS models in cluster approach can enhance the system productivity and income of farmers substantially while reduces the dependence on external farm inputs.